2005
DOI: 10.1242/dev.01950
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb group protein complexes exchange rapidly in livingDrosophila

Abstract: Fluorescence recovery after photobleaching (FRAP) microscopy was used to determine the kinetic properties of Polycomb group (PcG) proteins in whole living Drosophila organisms (embryos) and tissues (wing imaginal discs and salivary glands). PcG genes are essential genes in higher eukaryotes responsible for the maintenance of the spatially distinct repression of developmentally important regulators such as the homeotic genes. Their absence, as well as overexpression, causes transformations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 71 publications
(97 reference statements)
10
102
0
1
Order By: Relevance
“…This interpretation is consistent with the observation that a large fraction of CBX proteins is highly mobile in undifferentiated ES cells and in Drosophila embryos (26,28). The CBX proteins that are not chromatin associated could be recruited to new target genes during differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…This interpretation is consistent with the observation that a large fraction of CBX proteins is highly mobile in undifferentiated ES cells and in Drosophila embryos (26,28). The CBX proteins that are not chromatin associated could be recruited to new target genes during differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…Although dRYBP mutations alone do not result in homeotic-like phenotypes, they do when in combination with mutations in some PcG and trxG genes. We have found that the dRYBP protein is localized in a nuclear pattern and colocalizes with some of the Polycomb nuclear bodies (Buchenau et al 1998;Saurin et al 1998;Netter et al 2001;Ficz et al 2005;Grimaud et al 2006a). Moreover, the protein is dynamically distributed during the mitotic cycle in the syncytial embryo.…”
Section: P Attern Formation During Animal Developmentmentioning
confidence: 89%
“…For example, the transcription factor C/EBPα localized to regions of constitutive heterochromatin in mouse cells where it interacted with HP1α as part of a metastable protein complex. Although typically associated with transcriptional silencing 7,8 , a number of different transcription factors are known to preferentially localize to regions of centromeric heterochromatin 4,[9][10][11][12][13][14][15][16][17] . These associations may function to establish cell-specific patterns of gene expression 4,5,10 .…”
Section: Discussionmentioning
confidence: 99%
“…These regions of chromatin are marked by several different proteins, including HP1α, and are typically associated with transcriptional silencing 7,8 factors are also found associated with these intranuclear sites 9-11 . For example, the transcription factor C/EBPα, which has a role in the differentiation of many cell types 12 , localizes to regions of centromeric heterochromatin [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation